PENGARUH KETERAMPILAN KOMUNIKASI KEPALA SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI LISANPURO 2 KOTA MALANG - Dwiana Mustawan, Made (Widya Aksara, 2019)
This study aims to determine the "Influence of Principal Communication Skills on Teacher Performance in Lisanpuro 2 Elementary School in Malang City" which is motivated by the allegations about the decline in teacher performance in Lisanpuro 2 Elementary School in Malang. This is caused by several factors, one of which is the communication skills of the Principal. From the formulation and objectives of the research that is referring to issues related to the influence of the principal's communication skills on teacher performance. Theories used in this research are the theory of health and motivation theory. This type of research is associative descriptive quantitative research. Collecting data in this study using a questionnaire method (questionnaire), which each instrument is said to be valid through testing the construct validity (contruct validity) by the opinions of experts (Judgment Experts), the method of observation and documentation. The sampling technique is based on certain criteria, amounting to 70 people. Then the data analysis prerequisite test is carried out to determine the data normality and linearity of the data, then the data is analyzed using simple linear regression with a significance level of 5%. The results obtained are: 1) The communication skills of the principal in Lisanpuro 2 Public Elementary School in Malang are quite good, because the results of the study prove that of 70 respondents there were 38 data that had an average value of 135.61 and 32 data that has a value below the mean (mean) of 35.61. 2) The performance of teachers in Lisanpuro 2 Public Elementary School in Malang is good, because the results of the study prove that of 70 respondents there were 38 data that had a value above the mean (132.73) and 32 data that had values ??below the average ( mean) 132.73. 3) Principal's communication skills significantly influence the performance of teachers in Lisanpuro 2 Public Elementary School in Malang, this can be seen from the calculated value greater than the table: 43,328 is greater than 1,671. The contribution of the principal's communication skills variable to teacher performance by 96.5% was positively contributing and the remaining 3.5% was determined by other factors. It can be concluded that increasing the communication skills of the principal will be followed by an increase in the performance of teachers in the Lisanpuro 2 Public Elementary School in Malang.